PENYULUHAN HUKUM TENTANG PROBLEMATIKA PERKAWINAN DIBAWAH UMUR DI SMKN 2 TANAH PUTIH KABUPATEN ROKAN HILIR - Apriani, Desi; Kurniasih, Esy; Febrian, Rojja; Milandry, Anggraini Dwi (Universitas Kadiri, 2023)
The purpose of this community service is to provide socialization, understanding, and provision of knowledge and actual information related to the problems of underage marriage both in theoretical and practical terms. The main problem faced by partners is that partner communities (both educators and students) don’t really understand the problems of underage marriage, because the information obtained are still makes them confused, besides schools are one of the effective and closest forums to the community to be able to